Conservation of genetic resources of conifers in Spain - Martín Albertos, S.; González Martínez, S. C. (Forest Systems, 2000)
In the framework of biodiversity conservation, the inventory and conservation of forest genetics resources is a priority. In this work, the information available about quantitative and molecular variation in the species of genus Pinus, Abies, Juniperus, Tetraclinis and Taxus occurring in Spain is reviewed. In addition, the state of the on-going inventory and conservation of genetic resources is described (provenance areas, seed sources, seed orchards, clonal banks and seed banks, mainly). Ecology of the species, specific threats and the political framework are taking into account in the development of conservation strategies of forest genetic resources. In situ conservation both of pure stands and complex forest systems for all conifer species, ex situ conservation of the species of the genus Pinus in seed banks, and the importance of plantations, are highlighted.